Analisis Perbandingan Bacaan Jahar Dan Sir Ibadah Doa Dan Zikir Dalam al-Qur’an dan Hadis - Muhammad Shulhi Alhadi Siregar; Ermila Susanti Harahap (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Dhikr and prayer in prayer if the argument is jahar, if sir is combed, don't exchange it back. The reward of sir or jahar if it is based on the same argument as the jahar and sir prayer. The size of mad when jahar is the same as when sir and the reward is the same. Not adding to the size of the mad, adding to the thigh, quite the opposite, because it violates the rules of the science of tajwid. How to practice remembrance and prayer follow the arguments when praying or outside prayer. Amplifying your voice will disturb other friends, something that interferes is certainly wrong, there is nothing to be disturbed, either during ziki prayers and other worship.